Differences in sexual behavior between male and female bood donors (BD) in Salvador, Bahia, Brazil - additional evidence for a higher efficience of male-to-female sexual transmission of HTLV-1 infection - Mota, Augusto César de Andrade (2006)
FAPESB, CNPq, SESAB.